Studies on megacinogeny in Bacillus cereus. II. Bacillus cereus isolates characterized by prophage-controlled production of megacin A (phospholipase A) - Ivanovics G (ACTA MICROBIOLOGICA ACADEMIAE SCIENTIARUM HUNGARICAE, 1976)
Five out of a number of Bacillus cereus strains isolated from soil produced high titre specific bacteriocin (megacin A) in mitomycin C-induced cultures. In the course of cultivation with ethidium bromide, the strains gave off segregants not producing bacteriocin (cin-). The lysate of two wild strains formed plaques on the corresponding cin- bacteria. The two phages (wx23 and wx26) were identical in antigenic structure with phage wx was present in the lysate of B. cereus strain W, and converted cin- derivatives into cultures producing megacin A (phospholipase A). The phages produced plaques at 26 degrees C but not at 37 degrees C. In the lysates of the remaining three strains phages were not detected with biological and morphological methods; these cultures have been assumed to carry defective prophage genome. As the corresponding prophages are responsible for the determination of inducible phospholipase A production, phages named wx seem to form a separate group of B. cereus phages.